Tauhid Sebagai Prinsip Ilmu Pengetahuan (Studi Analisis Ismail Raji al Faruqi) - Firda Inayah (Universitas Darussalam Gontor, 2018)
This writing discusses the consept of tauhid in building science incorporated as part of al-Faruqi’s construction of Islamic studies. As a contemporary Muslim thinker, al-Faruqi maintains that tauhid is a substantial point in human’s character building in various dimensions. As such, this gives rise to producing the dynamics of tauhid meanings in all aspects of life. This kind of tauhid essence has to be persued at the ontological and epistemological conceptions. In order to explore such subtance, historical descriptive analysis approach is used so that the formulation of tauhid epistemology of al Faruqi could be known in detail throw light into the tauhid meanings in this life. The writer found that al-Faruqi’s scientific paradigm at the level of applying tauhid be demonstrated in the concept of science, hoping that it will enlighten human life based on the principles of Islamic creed or tauhid.